Hubungan Stigma dengan Kepatuhan Pengobatan Tuberkulosis Paru di Kota Lhokseumawe - Abi Fauzan Pulungan; Cut Khairunnisa; Nina Herlina (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis. Indonesia is one of the countries with the highest number of TB cases in the world. The key to successful TB treatment is treatment adherence. One factor that influences treatment adherence is stigma, which can result in incomplete treatment. This study aimed to determine the relationship between stigma and adherence to pulmonary TB treatment in the city of Lhokseumawe. The research method used was descriptive correlational with a cross-sectional approach. The sampling method was quota sampling with a sample size of 83 pulmonary TB patients. Data were filled in by filling out the Internalized Stigma of Mental Illness (ISMI) scale and Morisky Medication Adherence Scale (MMAS-8) questionnaires, and the data were analyzed using the Spearman correlation test (p = 0.05). The results of the bivariate test of age, gender, last education, occupation, and PMO did not have a relationship with adherence to pulmonary TB treatment, with a p value> 0.05. However, the duration of treatment had a relationship with the level of adherence to pulmonary TB treatment, with a p-value = 0.008. The study's results also showed that stigma and treatment compliance did not have a significant relationship, with p-value = 0.197. It was concluded that there was no relationship between stigma and compliance with pulmonary TB treatment. Health services in Lhokseumawe City are expected to continue to provide education and motivation to pulmonary TB patients to comply with their treatment.